(untitled) (Palíndromo, 2013)
Developed over a philosophical and a esthetic approach, this article analyzes, at first, the tale A Descent in to the Maelström, by Edgar Allan Poe, working through the photographic instant concept the Idea of vertigo from the literary image. Subsequently, such concept is explored by the pictoric object The Incredulity of Saint Thomas by Caravaggioin which the photographic instante merges from the blazing confrontation between the tangible and the visible, staging there of the silence of the world. Finally, the vídeo Sal e Prata by Rodrigo Braga is analyzed, where the photographic instant arises in na intermittent way reflecting the dicho to my of ones elf that do not cease to seek his lost count er partin the profuse Field of digital images, mistaking himself, consequently, by what is extrinsic to him.